Discourse Markers s Sentence Openers in Legal English - Onorina Botezat (EIRP Proceedings, 2010)
Discourse markers can be defined as linguistic expressions of different length which carry pragmatic and propositional meaning, they are used to combine clauses or to connect sentence elements andthey appear in both speech and writing, and facilitate the discourse. Each discourse marker indicates a particular meaning relationship between two or more clauses. English is predominantly the language ofinternational legal practice and its importance to lawyers cannot be over-emphasized. The way in which one uses legal English can therefore be crucial to professional success. This paper stresses the importance of good usage of discourse markers in legal English.